To Study the Prevalence and Pattern of Resistance and Sensitivity of Commonly Isolated Organisms in Patients Admitted In Surgical Intensive Care - Tantry Tariq Gani, Shoiab Bashir Khanday, Areeba Noor Shah; Sheikh Viqar Manzoor, Naseer Bashir Khanday, Asma Bashir Khanday (International Journal of Innovative Research in Medical Science, 2017)
Introduction: Nosocomial infections effect more than 2 million patients annually at a cost of US 4.5 billion. Intensive care units (ICU’s) patients are more vulnerable for development of these infections compared with an average patient. This study was conducted to know the prevalence and pattern of resistance and sensitivity of commonly isolated organisms in patients admitted in ICU’s of a tertiary care hospital. Material and methods: The patients developing ICU infections within 48 hours of admission in ICU or within 48 hours of transfer from ICU were included. Depending upon the clinical suspension Laboratory samples like urine, pus, blood, endotracheal suction catheter samples and central line tip culture samples were collected. The samples collected from ICU unit were inoculated on 5% sheep blood agar and MacConkey agar plates and incubated overnight at 370C aerobically. Bacterial pathogens were identified by Conventional Biochemical methods according to standard microbial techniques. Results: Forty patients with mean age of 51.43 ± 12.87 years showing different types of infections were included in this study. 92 samples including blood, urine, swab, sputum, pus and ETT samples were collected. A total of 10 types of micro-organisms were isolated with maximum number of micro-organisms were isolated from swab. Further, among ten micro-organisms isolated, the highest percentage was recorded for Pseudomonas spp. A total of 17 antibiotics were used to workout the sensitivity/resistance pattern of various micro-organisms. Among the various antibiotics used, imipenem, amikacin, nitrofurantoin, gentamicin, pipracillin-tazobactam and ceftazidime were found highly sensitive to most of the micro-organisms isolated. Conclusion: Most of the Gram negative isolates were multiply resistant to commonly prescribed antimicrobial agents. Hence, for proper management of critically ill patients in ICUs, hospital antibiotic policies need frequent revisions.